2016
DOI: 10.1039/c6re00020g
|View full text |Cite|
|
Sign up to set email alerts
|

Controlled generation and use of CO in flow

Abstract: A tube-in-tube flow reactor allows the generation and immediate use of CO, without the need for CO cylinders.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
20
0

Year Published

2017
2017
2023
2023

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 27 publications
(20 citation statements)
references
References 24 publications
(29 reference statements)
0
20
0
Order By: Relevance
“…More recently,L ey and co-workers reporteda na lternative reactions ystem for generating CO within the tube-in-tube reactor (Scheme1b). [25] Oxalyl chloride (COCl) 2 (4)w as hydrolyzed by sodium hydroxide (NaOH)w ithin the outer channel of the tube-in-tube reactor.T he use of an Omnifitc olumn (0.68 mL) with two magnetic stirrer bars prior to the tube-intube reactorw as necessary to adequately mix the toluene phase containing COCl 2 and the aqueous NaOH phase. CO then passed through the membrane into the inner tube for the main organic transformation which was flowing counterflow to the CO generating stream.…”
Section: Carbonmonoxide (Co)mentioning
confidence: 99%
“…More recently,L ey and co-workers reporteda na lternative reactions ystem for generating CO within the tube-in-tube reactor (Scheme1b). [25] Oxalyl chloride (COCl) 2 (4)w as hydrolyzed by sodium hydroxide (NaOH)w ithin the outer channel of the tube-in-tube reactor.T he use of an Omnifitc olumn (0.68 mL) with two magnetic stirrer bars prior to the tube-intube reactorw as necessary to adequately mix the toluene phase containing COCl 2 and the aqueous NaOH phase. CO then passed through the membrane into the inner tube for the main organic transformation which was flowing counterflow to the CO generating stream.…”
Section: Carbonmonoxide (Co)mentioning
confidence: 99%
“…A 'tube-in-tube' reactor was also utilised in the controlled generation and use of carbon monoxide in Pd-catalysed carbonylation reactions by Ley et al 40 The generation of CO was achieved by safe hydrolysis of oxalyl chloride using an aqueous NaOH solution in the first part of the flow reactor setup. The 'tube-in-tube' reactor was used to enrich a reaction stream with CO in the second part of the flow platform.…”
Section: Scheme 25 Flow Carbonylation Of Sterically Hindered Ortho-sumentioning
confidence: 99%
“…The tube‐in‐tube flow reactor was successfully applied for hydroformylation and some carbonylation reactions but not specifically for reductive carbonylation reactions . Furthermore, Ley and co‐workers recently showed that oxalyl chloride can be hydrolyzed by using NaOH to form CO in situ in flow and subsequently used the generated CO in carbonylation reactions . The aforementioned strategies are good options for research‐scale experimentation; however, both approaches suffer from limited scalability in terms of atom inefficiency, poorer performance at scale‐up, or are simply too expensive …”
Section: Introductionmentioning
confidence: 99%
“…[14] Furthermore, Ley and co-workersr ecently showed that oxalyl chloridec an be hydrolyzed by using NaOH to form CO in situ in flow and subsequently used the generatedC Oi nc arbonylation reactions. [15] The aforementioned strategies are good options for research-scale experimentation; however, both approaches suffer from limited scalability in terms of atom inefficiency,p oorer performance at scale-up, or are simply too expensive. [16,17] Tubular plug flow reactors have emerged as ap latform for the safe, efficient, and scalable utilization of gases direct from gas cylinders by using mass-flow controllers.…”
Section: Introductionmentioning
confidence: 99%